Quantitative flavonoid variations of Artemisia vulgaris L. and Veronica chamaedrys L. in relation to altitude and polluted environment - Nikolova, Milena T.; Ivancheva, Stephanie V. (Acta Biologica Szegediensis, 2005)
Influence of altitudinal gradient and polluted environment on externally accumulated flavonoid aglycones were examined. Contents of apigenin in Veronica chamaedrys L. and quercetin 3,7,3’-trimethyl ether in Artemisia vulgaris L. were determinated. The highest apigenin level was found in populations at alpine regions, whereas no relation was found between quercetin 3,7,3’-trimethyl ether and altitude. The largest amounts of quercetin 3,7,3’-trimethyl ether was found in samples collected from industrial polluted habitats. Ecological significance on external flavonoid aglycones is discussed.